Tunable Resistorless Phase Shifter Realization with a Single VDGA - Orapin Channumsin; Jirapun Pimpol; Tattaya Pukkalanun; Worapong Tangsrirat (Advances in Science Technology and Engineering Systems Journal, 2023)
This paper describes the design of a phase shifter with electrically adjustable parameters employing only one voltage differencing gain amplifier (VDGA) and one floating capacitor. This circuit requires no external resistors, resulting in a resistorless design and a low component count. The proposed circuit implements a first-order all-pass filter response with electronic control of its passband gain, pole frequency, and phase difference via bias current modification. Non-ideal effects of the VDGA on the phase shifter circuit are also examined. PSPICE simulation results using TSMC 0.25-m real process parameters and practical test results using readily available LM13700s are incorporated to validate the theoretical conclusions. The results indicate that the simulations and experiments yielded phase shift deviations of 2.22% and 3.11%, respectively. The pole-frequency errors for simulations and experiments were 0.31% and 0.63%, respectively. The applicability of the suggested phase shifter is illustrated by the design of the voltage-mode quadrature oscillator.
Keywords: Radio Frequency Integrated Circuit Design; Advanced DC-DC Converters; Silicon Carbide Semiconductor Technologies